2020
DOI: 10.1063/5.0023175
|View full text |Cite
|
Sign up to set email alerts
|

Orbital-fluctuation freezing and magnetic-nonmagnetic phase transition in α-TiBr3

Abstract: We present a detailed study on the structural phase transition in α-TiBr3, which is deeply connected with the lattice and orbital degree of freedoms. A chemical vapor transport method is adopted to synthesize the α-TiBr3 single crystal samples, and the structural phase transition at about 180 K is characterized by x-ray diffraction (XRD), magnetic susceptibility, and specific heat capacity. To further the understanding in the physical nature of this phase transition, a systematic Raman spectroscopic study is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…51,52 This may be due to metal dimerization. [53][54][55] Although this is neglected in this paper, it can be based on the hypothesis that the reduction of Ti-Ti bond length leads to an enhanced AFM of direct exchange interactions, making the system AFM or paramagnetic. Recently, some theoretical works predict that TiCl 3 and TiI 3 are ferromagnets with higher Curie temperatures than CrI 3 .…”
Section: Resultsmentioning
confidence: 99%
“…51,52 This may be due to metal dimerization. [53][54][55] Although this is neglected in this paper, it can be based on the hypothesis that the reduction of Ti-Ti bond length leads to an enhanced AFM of direct exchange interactions, making the system AFM or paramagnetic. Recently, some theoretical works predict that TiCl 3 and TiI 3 are ferromagnets with higher Curie temperatures than CrI 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In this work we performed a detailed spectroscopic and computational analysis of α-MoCl 3 with particular focus on the Mo-Mo bonding. Intertwining of structural and electronic properties necessarily involves phonon degrees of freedom, making vibrational and especially Raman spectroscopy a powerful tool in such an endeavor [18,[27][28][29][30]. Varying the Raman excitation laser wavelengths, we found that Mo-Mo stretching undergoes strong resonant enhancement when excitation matches electronic transitions between σ-bonding and σ * -antibonding orbitals of Mo-Mo dimers.…”
Section: Introductionmentioning
confidence: 89%
“…The delocalization-localization balance in layered transition metal compounds and the propensity for dimerization are very ubiquitous phenomena, which have a dramatic influence on their physical properties [13][14][15]. Formation of dimers with metal-metal bonds in MX 3 group was observed in α-TiCl 3 [16,17], α-TiBr 3 [18,19], β-TcCl 3 [20,21], α-RuCl 3 [22,23], and α-MoCl 3 (figure 1) [24][25][26]. While dimerization in RuCl 3 happens only under increased pressure, other listed halides can support M-M bonds under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Cation dimerization in a honeycomb lattice system has been reported in some halides (α-TiCl 3 , 14,15 α-TiBr 3 , 15,16 β-TcCl 3 , 17 α-MoCl 3 , 18 and α-RuCl 3 ) 19 and some oxides (Li 2 RuO 3 , 20 α-Li 2 IrO 3 , 21 and Cu 2 IrO 3 ). 22 This transition occurred only under high-pressure conditions in α-RuCl 3 , 19 α-Li 2 IrO 3 , 21 and Cu 2 IrO 3 .…”
mentioning
confidence: 94%